Goal-based ultimatum game - Zabidi, Nerda Zura; Sulaiman, Nor Intan Saniah; Zainal Abidin, Norhaslinda (2014)
This research investigates the human decision-making in ultimatum game in the context of neuroscience theories that give more insight into decision-making process by humans. Based on this approach, a new model of human decision-making has been developed by using Goal Programming approach. The satisficing and egalitarian philosophies on which weighted and Chebyshev Goal Programming (GP) rely; seem to offer an adequate and natural way for modeling human decision processes in at least the single-shot games of coordination. The simulation of ultimatum games gives the distribution of proposers' offer which shows some similarity with the distribution from the experiments with real subjects. The sensitivity analyses of this model are also presented. The solutions returned by the proposed GP approach aim to strike the right balance on several dimensions of conflicting goal that are set by players themselves.